CONCERNS ABOUT THE SCHOLARLY DEVELOPMENT OF THE NURSING PROFESSION AND THE ACADEMIC NURSING PIPELINE - Ryder, Mary; Connolly, Michael; Kitson, Alison L.; Thompson, David R.; Timmins, Fiona (Cogitare Enfermagem, 2023)
Editorial